The effect of political brand religious image and religious-secular divide on voters citizenship behavior - Nor Asiah Omar; Farhan, Akhmad; Syed Shah Alam; Syadiyah Abdul Shukor; Farhana Sidek (Penerbit Universiti Kebangsaan Malaysia, 2021)
Considerable evidence shows that religion-secular divide has become an important issue in modern politics which plays a crucial role in voters’ decision-making processes. As more political parties applying marketing concepts and strategies to motivate voters, this study aims to examine the role of political brand religious image (PBRIM) in influencing voters’ citizenship behavior (VCB) and sought to determine whether or not there are any differences between the citizenship behavior of religious and secular voters. This study used social credibility theory to underpin the relationship between variables. The data was collected from 520 voters in Indonesia who participated in the 2014 presidential election. A quota sampling technique and a drop-off and collect survey distribution approach were used in this study. The relationship between PBRIM and VCB (feedback, advocacy, help, and tolerance) was examined using Partial Least Squares Structural Equation Modelling (SmartPLS-SEM). Findings revealed that there is a significant, positive relationship between PBRIM and the dimensions of VCB. Besides that, there was a significant difference between political parties’ religious and secular images with all the four dimensions of voter’s citizenship behavior namely, advocacy, helping, feedback and tolerance behavior. Although both secular and religious voters are motivated to citizenship behavior, religious voters showed more inclination towards advocacy, tolerance, and helping behaviors. The findings of this research contributed to the body of knowledge in political marketing research by considering the political parties’ religious image in branding metrics. The revealed relationship will help the political parties to design their election campaign for ensuring voters support.